Content validation of the Self-perception of Family Health Status scale using the Delphi technique - Joaquín Salvador Lima-Rodríguez (Revista Latino-Americana de Enfermagem, 2013)
Objective: To ascertain the content validity of the Self-perception of Family Health Status scale. Method: A validation study of an instrument with an online Delphi panel using the consensus technique. Eighteen experts in the subject were intentionally selected, with a multidisciplinary origin and representing different professional fields. Each of the proposed items was assessed using a five-point scale, and open-ended questions, to modify or propose items. Descriptive analysis was performed of the sample and the items, applying criteria of validation/elimination. Results: The first round had a response rate of 83.3% and validated 75 of the 96 proposed items; the second had a response rate of 80%, and validated the 21 newly created items, concluding the panel of experts. Conclusions: We present an instrument to measure self-perception of family health status, from a nursing perspective. This may be an advance in scientific knowledge, to facilitate the assessment of the state of health of the family unit, enabling detection of alterations, and to facilitate interventions to prevent consequences to the family unit and its members. It can be used in clinical care, research or teaching.